Paxillin promotes tumor progression and predicts survival and relapse in oral cavity squamous cell carcinoma by microRNA-218 targeting - Wu, De-Wei; Chuang, Chun-Yi; Lin, Wea-Long; Sung, Wen-Wei; Cheng, Ya-Wen; Lee, Huei (Carcinogenesis (New York), 2014)
High-risk human papillomavirus (HPV) 16-infected oral cavity squamous cell carcinoma (OCSCC) differs significantly from non-HPV-infected OCSCC. However, the molecular pathogenesis of HPV-infected OCSCC remains unclear. Paxillin (PXN) has been reported to promote lung tumor progression by miR-218 targeting. In addition, expression of miR-218 has been shown to be reduced by HPV16 E6 in cervical cancer. We thus asked whether PXN can promote tumor progression by E6-reduced miR-218 in OCSCC, especially in HPV-infected OCSCC. Mechanistic studies demonstrated that PXN expression increased markedly upon E6-mediated reductions in miR-218, resulting in increased colony formation and invasion capabilities in HPV-infected OCSCC cells. Among tumor specimens, HPV16/18 infection was negatively associated with miR-218 expression and positively associated with PXN expression. Kaplan-Meier and Cox regression models demonstrated that patients with low-miR-218 tumors or high-PXN tumors exhibited shorter overall survival (OS) and relapse-free survival (RFS) than those with high-miR-218 tumors or low-PXN tumors. Interestingly, HPV-infected patients with low-miR-218, high-PXN tumors and both combinations exhibited the worst OS and RFS compared with patients in their counterparts. These observations in patients were consistent with the findings from the cell model. Therefore, we suggest that PXN might be targeted to suppress tumor progression and consequently to improve outcomes in OCSCC, especially in HPV-infected OCSCC.